The endowment model of investing : return, risk, and diversification - Leibowitz, Martin L., 1936- (John Wiley & Sons, 2010)
A cutting-edge look at the endowment model of investing. Many larger endowments and foundations have adopted a broadly diversified asset allocation strategy with only a small amount of traditional U.S. equities and bonds. This technique, known as the "endowment model of investing," has demonstrated consistent long-term performance and attracted the attention of numerous institutional and individual investors. With The Endowment Model of Investing Leibowitz, Bova, and Hammond take a closer look at the endowment model with customary research sophistication and attention to detail. Thro